2013
DOI: 10.1016/j.ultsonch.2012.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Instant controlled pressure drop technology and ultrasound assisted extraction for sequential extraction of essential oil and antioxidants

Abstract: The instant controlled pressure drop (DIC) technology enabled both the extraction of essential oil and the expansion of the matrix itself which improved solvent extraction. The sequential use of DIC and Ultrasound Assisted Extraction (UAE) triggered complementary actions materialized by supplementary effects. We visualized these combination impacts by comparing them to standard techniques: Hydrodistillation (HD) and Solvent Extraction (SE). First, the extraction of orange peel Essential Oils (EO) was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…Expansion affects the olive leaf structure and cell walls, which make solvent extraction easier. Several recent studies showed similar results[17,18,28].…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Expansion affects the olive leaf structure and cell walls, which make solvent extraction easier. Several recent studies showed similar results[17,18,28].…”
supporting
confidence: 63%
“…The DIC treatment was used as an intensifying treatment for the extraction of different molecules such as flavonoids [20], essential oils [18,19], oligosaccharides [27] and antioxidants [28].…”
Section: Effect Of Dic Treatment On Total Polyphenols Yieldmentioning
confidence: 99%
“…This was observed and explained in terms of fundamental and experimental aspects. Indeed studies were reported for Kananga flowers (Kristiawan, Sobolik, & Allaf, 2008), lavandin , myrtle leaves (Berka-Zougali, Hassani, , orange peel (Allaf, Tomao, Ruiz, & Chemat, 2013), etc. providing very relevant results in terms of essential oil extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has been used to extract antioxidants from many food materials including seeds. Ultrasound and ultrasoundassisted extractions use sound waves to produce cavitation microbubbles that collapse violently in the sample and facilitate the release and extraction of several compounds [23][24][25]. Some researchers had evaluated ultrasound-assisted extraction, in an open system, using a sonicator probe directly on the liquid sample to obtain seed oil from flaxseed [26], Korean pine [27], and pomegranate [28].…”
Section: Introductionmentioning
confidence: 99%